How Can We Not Waste Legacy Genomic Research Data? - Wallace, Susan E.; Kirby, Emily; Knoppers, Bartha Maria (Frontiers in Genetics, 2020)
Enabling genomic and biomedical data to be shared for secondary research purposes is not always straightforward for existing ‘legacy’ data sets. Researchers may not know whether their data meet ethical and regulatory requirements for sharing. As a result, these data, collected using public funds and the good will and efforts of the donors and investigators, may not be used beyond their original purpose. Single-use plastics are now being banned in many countries; single-use research should be avoided if possible. This paper describes a filter developed through the driver projects of the Global Alliance for Genomics and Health that can be used by researchers to help them determine the extent of sharing possible for their legacy data and actions to be taken to enable further sharing.